2017
DOI: 10.1038/s41598-017-12106-y
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effects of ipragliflozin on behaviour and energy homeostasis in normal and type 2 diabetic rats: continuous glucose telemetry analysis

Abstract: Sodium–glucose cotransporter 2 (SGLT2) inhibitors are oral antidiabetic drugs that promote urinary glucose excretion. Conversely, they cause behavioural changes, such as hyperphagia, that result in a positive energy balance. The relationship between energy homeostasis and SGLT2 inhibitors-induced behavioural changes remains unclear. Here we show that ipragliflozin, a SGLT2 inhibitor, time-dependently affects behaviour and enhances energy expenditure in normal and type 2 diabetic Goto–Kakizaki (GK) rats, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Treatment with SGLT2 inhibitors decreases consumption of energy from glucose, while compensatorily increasing consumption of energy from fat 23. As a result, total energy expenditure is increased, as seen in our study and others,13 29 or remains unchanged 20 22 23. The discordance in the impact of SGLT2 inhibitors on energy expenditure among published reports may be due to differences in experimental conditions, such as the dose of inhibitor, body mass of animals (lean or obese) and timing of energy expenditure measurements.…”
Section: Discussionsupporting
confidence: 63%
“…Treatment with SGLT2 inhibitors decreases consumption of energy from glucose, while compensatorily increasing consumption of energy from fat 23. As a result, total energy expenditure is increased, as seen in our study and others,13 29 or remains unchanged 20 22 23. The discordance in the impact of SGLT2 inhibitors on energy expenditure among published reports may be due to differences in experimental conditions, such as the dose of inhibitor, body mass of animals (lean or obese) and timing of energy expenditure measurements.…”
Section: Discussionsupporting
confidence: 63%
“…74) Recently, we reported that SGLT-2 inhibitors improved GV in a T2DM model, which may be one of the factors related to the improved BRS in animal studies. 75) We also conducted a prospective study of the effects of 3 months of treatment with a SGLT-2 inhibitor on BRS in patients with T2DM and showed that SGLT-2 inhibitors do not worsen BRS despite their diuretic effect. 76) A large percentage of patients with T2DM have complications of obesity, 13,22) hypertension, 13,15,33) dyslipidemia, 15,18,77) and chronic kidney disease, 78) which affect BRS, but as SGLT-2 inhibitors, unlike other antidiabetic drugs, have the effect of comprehensively ameliorating these complications, their efficacy in reducing BRS is expected.…”
Section: Brs and Variability Of Blood Glucosementioning
confidence: 99%
“…The latter is due to a strong reduction in blood glucose in response to SGLT2 inhibition in these models, which together with the associated lowering in GFR, reduces filtered glucose load to a similar extent as the drugs inhibit proximal tubular glucose reabsorption, such that glucosuria and urine flow rate remain largely unchanged, consistent with mathematical modeling (Layton, Vallon, & Edwards, ). In comparison, non‐obesity type 2 diabetic Goto‐Kakizaki (GK) rats only have mild hyperglycemia and in this regard mimic patients with type 2 diabetes and likewise show a sustained increase in glucosuria and urine volume in response to SGLT2 inhibition (Iuchi et al, ). We therefore examined the effects of the SGLT2 inhibitor ipragliflozin on renal water handling in diabetic GK rats.…”
Section: Introductionmentioning
confidence: 99%